Aproveitamento da batata (Solanum tuberosum) para a produção de álcool - Arruda, Elis Renara Azambuja (2006)
A major part of the potato (Solanum tuberosum) production is rejected either during harvesting or grading, because of tuber size or defects. Potato is an important carbohydrate source as starch and sugars, which are used as row materials for alcohol production. Potato alcohol may be part of distilled beverages or used in chemical industry. The objective was to evaluate the effects of clone and tuber size in alcohol production to find marketable value for tubers rejected during harvesting or grading. The breeding clones SMIJ461-1 and SMINIA90244-3 and tuber sizes of bigger and smaller than 23mm were evaluated. Tuber samples were slashed, fermented and the liquid portion distilled. The solid-residual part of fermentation, the liquid-residual part of distillation and the produced alcohol were analyzed. Tuber dry matter and starch and reduced sugar contents were also determined. Alcohol samples were submitted to alcohol grade, density, total and volatile acidity, superior alcohols, esters, methanol and aldehyde determinations. The content of N, P, K, Ca, Mg, S, B, Cu, Fe, Mn and Zn were determined in the solid and liquid residues. Dry matter content was higher in big than small tubers of both clones. Distillation process increased starch content of both clones and tuber sizes. Similar alcohol yield was found in both potato clones and tuber sizes. The alcohol grade varied from 69,31°LG of big tubers to 78,44°LG of small tubers of SMINIA90244-3 clone. The alcohol grade of the SMIJ461-1 was 69,86°LG for small and 75,15°LG for big tubers. Methods of fermentation and distillation were more related to variations in chemical content of alcohol than clone or tuber size. Solid residue had higher content of minerals than liquid residue. Tuber physiological age does not affect yield and quality of alcohol.